ANALISIS EFEKTIVITAS TEORI HOLLAND DALAM MENINGKATKAN KEMATANGAN PENGAMBILAN KEPUTUSAN KARIER SISWA: TINJAUAN LITERATUR - Heldriyana, Risda; Zuzanti, Zakian (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the effectiveness of applying Hollands Theory in enhancing the career decision-making maturity of high school students. The research employs a qualitative method using a literature review approach, in which data were collected by examining various national and international studies published within the last five years, focusing on the influence of Hollands theory on adolescents career maturity. Based on the analysis of several studies (Fitriyah et al., 2023; Desvikayati et al., 2022; Jiman & Dharsana, 2024; Tarmuzi et al., 2024), the findings indicate that Hollands theory is effective in helping students develop self-understanding, identify their personality types based on the RIASEC model, and align them with appropriate occupational environments. Interventions derived from this theorysuch as individual career counseling, interest and personality assessments, and career information servicessignificantly contribute to improving students career maturity. However, its effectiveness is influenced by contextual factors, including school and family support as well as the availability of valid assessment instruments. This review concludes that Hollands theory remains relevant and adaptable to the dynamics of the modern world of work and can serve as a conceptual foundation for developing career guidance services in secondary education.Keyword: Holland's theory, career maturity, career decision making, high school studentsAbstrak: Penerapan teori Holland dalam meningkatkan kematangan pengambilan keputusan karir pada siswa sekolah menengah atas (SMA), penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur, atau disebut juga literature review. Data dikumpulkan dengan meninjau berbagai penelitian nasional dan internasional yang terbit dalam kurun waktu lima tahun terakhir, yang berfokus pada teori Holland tentang kematangan karir remaja. Beberapa kajian teori dari berbagai studi (Fitriyah et al., 2023; Desvikayati et al., 2022; Jiman & Dharsana, 2024; Tarmuzi et al., 2024), teori Holland terbukti efektif dalam membantu siswa memahami diri (self-understanding), mengenali jenis kepribadian berdasarkan model RIASEC, dan menyesuaikannya dengan lingkungan pekerjaan yang sesuai. Konseling karir individual, asesmen minat dan keperibadian, dan layanan informasi karir adalah intervensi berbasis teori ini yang meningkatkan kematangan karir siswa. Namun demikian, efektivitasnya dipengaruhi oleh faktor kontekstual, seperti dukungan sekolah, keluarga, serta ketersediaan instrumen asesmen yang valid. Studi ini menunjukan bahwa teori Holland masih relevan dan dapat disesuaikan dengan perubahan dunia kerja modern, oleh karena itu, dapat digunakan sebagai landasan konseptual untuk membangun layanan bimbingan karir disekolah menengah.Kata kunci: teori Holland, kematangan karir, pengambilan keputusan karir, siswa SMA